The Efficacy of Lumbar Traction versus Spinal Mobilization with Leg Movement in Patients with Lumbar Radiculopathy: A Randomized Controlled Trial - Mohamed Hussein ElGendy; Islam Tarek Abuemira; Ali Muhammad Al-Guyoushi; Efrem Kentiba; Magda Gayed Sedhom (Здоров’я, спорт, реабілітація)
Background and Purpose